A G-Net Based Environment for Logical and Timing Analysis of Software Systems - Perkusich, Angelo; Figueiredo, Jorge C. A. de (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1995: Anais do IX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1995.24087, 1995)
The application of Petri nets for the modeling and verification of systems, at specification and design levels are well know. Despite of powerful structuring mechanisms available in the Petri nets theory for the construction of the model of complex systems, the designer is still likely to face the problem of state explosion, when analyzing and verifying large systems. Also, when dealing with real-time systems, the verification of timing properties is necessary. A model, named G-Nets, and a time extension, named Fuzzy Time G-nets, were introduced to the the modular analysis of complex real-time software systems. In this work we introduce an environment for logical and timing analysis based on this two kind of Petri nets.